The Competencies Of Nurses And Midwives In Implementing The 10 LMKM In The Postpartum Inpatient Ward At “X” Hospital In South Tangerang City - Hikmah Kurniasari; Sumijatun Sumijatun; Nurmala Dewi Ria Lestari (Eduvest - Journal of Universal Studies, 2026)
Background: Ten Steps to Successful Breastfeeding (10 LMKM) places nurses and midwives as key actors in supporting the success of exclusive breastfeeding in hospitals, especially maternity care units that have not yet reached the 100% target. Competencies that include knowledge, clinical skills, and behavior of health workers are needed to support the sustainability of the 10 LMKM, but it is not yet known how the competencies of nurses and midwives in implementing the 10 LMKM in the postpartum inpatient room of “X” Hospital, South Tangerang City. Methods: This study is a qualitative study with a case study approach, using in-depth interviews with 3 managerial staff and 6 postpartum mothers, Focus Group Discussions with 3 nurses and 3 midwives, observation, and document review. Data analysis uses the Miles and Hubberman model with triangulation of sources and methods, processed thematically using NVivo software. Results: Adequate clinical knowledge and skills are technical in nature, reactive and unstructured educational practices, gaps between written policies and field practice, documentation of breastfeeding support care not yet a priority, and the need for independent information media and standardized educational materials. This situation has impacted breastfeeding education achievement, which has not yet reached 100%. Conclusions and recommendations: Nurses' and midwives' competencies are still technically oriented and require strengthening policy integration, proactive education, and monitoring systems to support the comprehensive implementation of the 10 LMKMs. This necessitates policy strengthening, ongoing training, systematic documentation, and monitoring.